Workload dan Work Life Balance Terhadap Turnover Intention Pada Generasi Z di Kota Bekasi - Dewi, Oktaviana Ratna Sari; Ekawaty, Novian (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2026)
This research aims to analyze the influence of workload and work-life balance on turnover intention among Generation Z employees in Bekasi City using a quantitative approach. At its core, this research addresses the structural and psychological difficulties Generation Z faces during their transition into professional life. Data were collected through questionnaires from 400 respondents aged 20 to 28 years, working as laborers, employees, or staff. The analysis was conducted using multiple linear regression and scale range measurements. The findings reveal that workload has a significant positive effect on turnover intention by 5.31%, while work-life balance has a significant negative effect of -23.87%. Simultaneously, both variables contribute 40.29% to turnover intention, while the remaining 59.71% is affected by other variables beyond this study. Companies are expected to formulate effective retention strategies to better manage the turnover intention among Generation Z employees in Bekasi City.